'To me, it's like a little box of tricks': Breaking the depressive interlock as a programme participant in mindfulness‐based cognitive therapy. (2nd September 2014) - Murphy, Helen; Lahtinen, Marika
<x xml:space="preserve">Abstract</x> Objectives Mindfulness meditation practices have become increasingly popular in clinical therapies, changing patterns of depressogenic thinking for individuals who experience consecutive episodes of depression. We were interested in finding out how mindfulness‐based cognitive therapy (MBCT) worked for programme participants by focussing on how meditative practices changed their relationships with their thoughts. Design Data for the study came from six semi‐structured research interviews carried out with individuals who had taken part in an 8‐week MBCT programme. Methods We used interpretative phenomenological analysis to analyse the experiential accounts. Results We report on two superordinate themes – Engaging the Neutral Mind (with subordinate themes 'breaking the paralysis of worry' and 'choosing to think differently') and Experiencing the Neutral Mind (with subordinate themes of 'reflection on previous thinking styles' and 'becoming psychologically self‐reliant'). Conclusions Themes from the present study offer support to the assertion that mindfulness meditation helps facilitate a different mode of meta‐cognitive processing with which to handle depression‐related cognitions. Practitioner points Participants reported that they experienced an enhanced capacity to differentiate between their thought processes, experiencing an ability to tolerate some more uncomfortable thoughts, and experiencing a/more choice in how to respond to thoughts. Participants recognized that ruminating over negative thoughts was related to depressive states and experienced a shift in meta‐cognitive processes that actively challenged depressogenic cognitions. Participants became more psychologically self‐reliant and therapeutically independent following MBCT. Integrating mindfulness‐based practices in therapy may be a mediating factor in sustaining psychological well‐being and may help clients develop self‐compassion. Future research looks to examining exit cases to understand elements of MBCT which are experienced as less successful by clients.